ANALYSIS OF THE RANGE OF MEDICINES USED TO TREAT COMMON OCCUPATIONAL DISEASES OF COAL INDUSTRY WORKERS - Петров, Андрей Георгиевич; Филимонов, Сергей Николаевич; Семенихин, Виктор Андреевич; Хорошилова, Ольга Владимировна; Танцерева, Ирина Герасимовна; Павлова, Вера Юрьевна (Medicine in Kuzbass, 2020)
The goal is to analyze the target segment of the pharmaceutical market of drugs for the treatment of common occupational diseases of coal industry workers and to identify the presence of various product items of the studied range, in order to assess the effectiveness of treatment and prevention. Materials and methods. The object of the study was a range of medicines for the treatment of the most common occupational diseases of coal industry workers: vibration disease (VD), sensorineural hearing loss (NST), chronic dust bronchitis (CPD), musculoskeletal system (ODA). To analyze the market range of this product range, we used methodological marketing approaches: analysis of the composition of active substances – international non-proprietary names (INN) of medicinal products, by country of origin, types of dosage forms; nosological forms of diseases (in this case, we consider certain occupational diseases (PZ) of coal industry workers; with the position belonging to the anatomical-therapeutic-chemical groups (ATC-classification), included in the List of vital and essential drugs (EDL), which has value when applying for pharmaceuticals in medical institutions, as well as quantitative and structural characteristics of the range LP: the number and proportion of trade names (TN), commodity pricing (TCP) for each MNN, approved for use in the Russian Federation. Results. Analysis of the assortment by release forms showed that the studied drugs for the treatment of PD are produced in various dosage forms (LF) of all main types and variants: solid, liquid, soft, gaseous, but the dominant amount of drugs is produced in solid LF. Tablets (46.4 %) and capsules (13.4 %) accounted for a significant share of solid LFS, injectable LFS accounted for a significant share (26.9 %), semi-finished LFS were presented in the form of powders for preparing solutions for parenteral administration or for preparing solutions for internal use. Gaseous forms in the form of aerosols accounted for 4.8 %. The analysis of the novelty of the studied assortment showed that out of 1480 product items of drugs intended for the treatment of these diseases, 53 product items were registered and included in the GRLS over the past three years, that is, they are relatively new. Conclusion. The results of the analysis of the range of medicines used for the treatment of common occupational diseases of coal industry workers are used to describe the medicinal product range of the region and create conditions for comparing data on the consumption of medicinal products at the national (regional) level. Standardized information about medicinal products is necessary in the Ministry of defense for auditing the structure of their consumption, conducting educational and other activities, and monitoring the final results.